The Mental Health of Caregivers and Their Patients With Dementia During the COVID-19 Pandemic: A Systematic Review - Carbone, Elvira Anna; de Filippis, Renato; Roberti, Roberta; Rania, Marianna; Destefano, Laura; Russo, Emilio; De Sarro, Giovambattista; Segura-Garcia, Cristina; De Fazio, Pasquale (Frontiers in Psychology, 2021)
Background: The Coronavirus Disease 2019 (COVID-19) is a public health concern worldwide. It continues to spread rapidly throughout the world causing multiple physical and psychological consequences in the population. Especially, people affected by severe psychiatric or neurological diseases are highly susceptible to serious health complications not only due to the direct effect of the infection but also to the indirect effect of COVID-19 following the social distancing during the lockdown and its general social consequences. Indeed, lockdown and difficulties to use the care services produced psychological consequences in caregivers as depression, anxiety and worsening of the quality of life which in turn affected the ability to manage patients. Our aim is to systematically review the psychological consequences of the COVID-19 lockdown in caregivers of patients with cognitive impairment and dementia and the impact on their patients’ health. Methods: A systematic literature search was conducted searching in MEDLINE/PubMed, Scopus and Web of Science by two independent researchers following the PRISMA statement guidelines. Data extraction and quality assessment was also performed. Papers were screened for eligibility by abstract and then those which met inclusion criteria were included in this review. Results: The initial search returned 410 records. After the abstracts screening and the inclusion/exclusion criteria were applied, 315 were excluded because irrelevant, 30 because they were reviews, meta-analyses, letters to editors, editorials, guidelines, or case reports and 10 duplicates. Then, 38 out of 55 abstracts/full-text articles were excluded because did not assess simultaneously patients’ and caregivers’ mental health. At the end, 17 papers were deemed eligible and included in the present review. Conclusion: Based on current literature, the COVID-19 pandemic and the ensuing lockdown caused severe psychological consequences for caregivers of patients with dementia, worsening their mental health and increasing the psychological and physical burden, independently from the severity of their relatives’ disease, which resulted also independently globally worsened.